COVID-19 findings in chest computed tomography - Calvi,Camila (2021)
SUMMARY OBJECTIVE: The aim of this study was to describe chest computed tomography image findings in patients with COVID-19. METHODS: The chest computed tomography scans of 453 hospitalized patients with confirmed COVID-19 were collected at two tertiary care Brazilian hospitals. Demographics and clinical data were extracted from the electronic record medical system. RESULTS: The main chest computed tomography findings were ground-glass opacities (92.5%), consolidation (79.2%), crazy-paving pattern (23.9%), parenchymal bands (50%), septal thickening (43.5%), and inverted halo sign (3.5%). Of the 453 hospitalized patients, 136 (30%) died. In this group, ground-glass opacities (94.1%), consolidation (89.7%), septal thickening (58.1%), crazy-paving pattern (52.2%), and parenchymal bands (39.7%) were the most common imaging findings. CONCLUSIONS: In a dynamic disease with a broad clinical spectrum such as COVID-19, radiologists can cooperate in a better patient management. On wisely indicated chest computed tomography scans, the fast identification of poor prognosis findings could advise patient management through hospital care facilities and clinical team decisions.